It is Important to Learn Polite Etiquette Through Civics Education Lessons in Elementary School - Widya Ramadani (International Journal of Students Education, 2024)
Citizenship Education (PKn) in Elementary Schools (SD) has an important role in forming good manners ethics in students. Even though it is not explicitly stated in the curriculum, polite behavior development is carried out incidentally by teachers through an integrated approach to learning. This research aims to understand how teachers foster polite ethics through Civics in elementary schools. The literature review method is used to analyze findings from related journals. The results of the research show that teachers pay special attention to students' polite behavior, provide examples of polite behavior in daily activities, motivate students to behave politely, and assess this behavior through direct observation during learning activities. Suggestions for increasing the effectiveness of Civics learning include conducting an in-depth analysis of the curriculum before designing learning, involving students in role plays after being given experience in polite behavior, and assessing students' success in displaying the expected behavior. By implementing these suggestions, it is hoped that Civics learning can become more effective in developing students' ethical and polite behavior in everyday life.